2020
DOI: 10.1038/s41388-020-1293-5
|View full text |Cite
|
Sign up to set email alerts
|

AMOTL1 enhances YAP1 stability and promotes YAP1-driven gastric oncogenesis

Abstract: Hippo signaling functions to limit cellular growth, but the aberrant nuclear accumulation of its downstream YAP1 leads to carcinogenesis. YAP1/TEAD complex activates the oncogenic downstream transcription, such as CTGF and c-Myc. How YAP1 is protected in the cytoplasm from ubiquitin-mediated degradation remains elusive. In this study, a member of Angiomotin (Motin) family, AMOTL1 (Angiomotin Like 1), was screened out as the only one to promote YAP1 nuclear accumulation by several clinical cohorts, which was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…Reports (Seo et al, 2016) have indicated that YAP1 activation can lead to EMT changes in renal tubular epithelial cells. In this study, we found that consistent with its involvement in the pathogenesis of tumors The expression of FGF2, p-STAT3, STAT3, and YAP1 in the renal tissues of mice in the sham, UUO, N + U, and A + U groups was detected by immunohistochemical staining (×200) (Anna et al 2016;Kang et al, 2018;Zhou et al, 2020), YAP1 promotes the transcription of CTGF, which is a key factor in the pathogenesis of TIF. In this study, we found that the FGF2/STAT3 pathway targeted YAP1 to promote EMT in renal tubular epithelial cells by promoting CTGF expression, which led to the occurrence of renal interstitial fibrosis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Reports (Seo et al, 2016) have indicated that YAP1 activation can lead to EMT changes in renal tubular epithelial cells. In this study, we found that consistent with its involvement in the pathogenesis of tumors The expression of FGF2, p-STAT3, STAT3, and YAP1 in the renal tissues of mice in the sham, UUO, N + U, and A + U groups was detected by immunohistochemical staining (×200) (Anna et al 2016;Kang et al, 2018;Zhou et al, 2020), YAP1 promotes the transcription of CTGF, which is a key factor in the pathogenesis of TIF. In this study, we found that the FGF2/STAT3 pathway targeted YAP1 to promote EMT in renal tubular epithelial cells by promoting CTGF expression, which led to the occurrence of renal interstitial fibrosis.…”
Section: Discussionsupporting
confidence: 66%
“…Yap/Taz activation has been reported to lead to ECM deposition and affect the development and progression of interstitial fibrosis in a mouse model of progressive TIF (Liang et al, 2017). In the pathogenesis of gastric cancer and breast cancer, YAP interacts with TEAD to regulate the transcription of its target gene connective tissue growth factor (CTGF), thus leading to the occurrence of tumors (Anna et al 2016;Kang et al, 2018;Zhou et al, 2020). CTGF is a key factor in renal fibrosis (Toda et al, 2018), and whether YAP1 can also promote the transcription of CTGF during the pathogenesis of renal interstitial fibrosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that miR-195/497 cluster decreased the formation of regulatory transcription complex containing Yap and Smad3, while decreasing their common target genes, such as the gene-encoding CTGF ( Luo, 2017 ). Various studies have revealed that CTGF is critical in cancer progression and initiation ( Chen et al, 2019 ; Pu et al, 2019 ; Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 In gastric cancer cells, AMOTL1 knockdown not only reduces cellular proliferation and invasion but also induces cell cycle arrest and cell apoptosis. 12 These findings collectively suggest that AMOTL1 has a cancer-promoting role. In line with these studies, our results showed that silencing AMOTL1 impeded and AMOTL1 overexpression enhanced glioma cell proliferation and invasion.…”
Section: Amotl1 Was Involved In Mediating Yap1 Activation In Gliomamentioning
confidence: 87%